2015
DOI: 10.1371/journal.pone.0128769
|View full text |Cite
|
Sign up to set email alerts
|

Repeat Associated Non-AUG Translation (RAN Translation) Dependent on Sequence Downstream of the ATXN2 CAG Repeat

Abstract: Spinocerebellar ataxia type 2 (SCA2) is a progressive autosomal dominant disorder caused by the expansion of a CAG tract in the ATXN2 gene. The SCA2 disease phenotype is characterized by cerebellar atrophy, gait ataxia, and slow saccades. ATXN2 mutation causes gains of toxic and normal functions of the ATXN2 gene product, ataxin-2, and abnormally slow Purkinje cell firing frequency. Previously we investigated features of ATXN2 controlling expression and noted expression differences for ATXN2 constructs with va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…However, recent evidence demonstrates that repeat length constitutes a major determinant influencing translation. While repeat length is often positively correlated with the levels of both AUG-initiated and RAN translation (Krans et al, 2016; Krauss et al, 2013; Scoles et al, 2015; Zu et al, 2011, 2013, 2017), RAN translation is only observed from transcripts with pathogenic repeats (Gaspar et al, 2000; Mori et al, 2013a; Todd et al, 2013; Zu et al, 2011, 2013). A similar dependence on pathogenic repeat length has been observed for frameshifting (Saffert et al, 2016).…”
Section: Non-canonical Translation Of Nucleotide Repeat Expansionsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent evidence demonstrates that repeat length constitutes a major determinant influencing translation. While repeat length is often positively correlated with the levels of both AUG-initiated and RAN translation (Krans et al, 2016; Krauss et al, 2013; Scoles et al, 2015; Zu et al, 2011, 2013, 2017), RAN translation is only observed from transcripts with pathogenic repeats (Gaspar et al, 2000; Mori et al, 2013a; Todd et al, 2013; Zu et al, 2011, 2013). A similar dependence on pathogenic repeat length has been observed for frameshifting (Saffert et al, 2016).…”
Section: Non-canonical Translation Of Nucleotide Repeat Expansionsmentioning
confidence: 99%
“…While poly(CAG) RAN translation was supported by a series of constructs with similar repeats but with unique upstream flanking sequences, the abundance and size of the RAN products varied, indicating translation initiates at multiple sites (Todd et al, 2013; Zu et al, 2011). In experiments comparing transcripts differing only in the presence or absence of an in-frame AUG codon upstream of the repeat, the presence of an AUG usually, but not always, resulted in greater translation, suggesting that some upstream sequences may influence start site selection by simply providing an in-frame AUG start codon (Bañez-Coronel et al, 2015; Kearse et al, 2016; Krans et al, 2016; Scoles et al, 2015; Todd et al, 2013; Zu et al, 2011, 2013). For RAN products that do not initiate within the repeat, upstream sequences are essential.…”
Section: Non-canonical Translation Of Nucleotide Repeat Expansionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This work has caused a turmoil in the field of DNA repeat expansions disorders, with new non-ATG proteins being reported in several neurodegenerative traits, rendering the field far more complex than it was first considered (Cleary and Ranum, 2014). In SCA2, this phenomenon was also observed for the ATXN2 gene, although in lower levels compared to canonical ATG translation and the study failed to detect polyserine and polyalanine proteins (Scoles et al, 2015). …”
Section: Disease Mechanisms Of Sca2mentioning
confidence: 86%
“…Repeat expansion diseases where this mechanism has been observed now include SCA2, SCA8, SCA31, HD, FXTAS/FXPOI, and C9FTD/ALS [9, 13, 27, 96, 129, 218, 261, 290, 339, 340]. RAN translation of xtrRNA sequence can occur in many contexts, including repeat expansions found in untranslated regions, retained introns, and even those embedded in coding exons [96].…”
Section: Nuclear Export and Translation Of Xtrrnamentioning
confidence: 99%